2017
DOI: 10.3892/etm.2017.5327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of naturally aging and D‑galactose induced aging model in beagle dogs

Abstract: Animal models have been used to study aging for decades. In numerous aging studies, beagles are the most commonly used breed of dog. However, few studies have compared between naturally aging models and experimentally induced aging models in beagle dogs. In the present study, a D-galactose induced aging model was compared with a naturally aging model, and young adult dogs were considered as the young control group. The level of malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GSH-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
4
25
0
5
Order By: Relevance
“…This showed that intraperitoneal administration of d ‐Galactose causes fibrosis in liver tissue. This result is in accordance with the study conducted by Ji et al () that d ‐Galactose causes oxidative stress in liver tissue by generating ROS. ROS stimulates the activation and proliferation of myofibroblasts which then produce collagen fiber excess in the tissue (Morry et al ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This showed that intraperitoneal administration of d ‐Galactose causes fibrosis in liver tissue. This result is in accordance with the study conducted by Ji et al () that d ‐Galactose causes oxidative stress in liver tissue by generating ROS. ROS stimulates the activation and proliferation of myofibroblasts which then produce collagen fiber excess in the tissue (Morry et al ).…”
Section: Discussionsupporting
confidence: 93%
“…d ‐galactose exposure can lead to an increase in MDA causing oxidative stress in various tissues (Ho et al ; Huang et al ). d ‐Galactose also contributes to the production of ROS and reacts with amino acids to form advanced glycation en d ‐products (AGE) which also occur in normal aging, particularly in the liver and brain (Parameshwaran et al ; Ji et al ). The present study aimed to investigate the effect of low and moderate treadmill exercise on liver of d ‐Galactose‐exposed aging rat model.…”
Section: Introductionmentioning
confidence: 99%
“…d-Gal can cause systematic ageing-related changes, such as hepatic and brain injury, a decline in immune function [26][27][28][29], learning and memory impairment, and fatigue in behavior studies [26,27]. Parallel histopathological features of the liver, spleen, and hippocampus were observed similarly in the d-gal-induced ageing and naturally aging groups [30]. The rate of binucleated hepatocytes increased with ageing [31].…”
Section: Discussionmentioning
confidence: 96%
“…While past studies have used a high-fat diet to induce aging, recent studies have shown that aging can also be accelerated via chronic administration of D-galactose, primarily via accumulation of reactive oxygen species, as well as through glycation of end products [17]. The D-galactose-induced model has also been reported to exhibit conditions similar to naturally aged animals [18]. Considering that we have found AMPK activation potentials of certain Lactobacillus strains, we hypothesized that some of these strains can also regulate lipid metabolism, alleviate hyperlipidemia, and restore liver conditions, such as that of steatosis.…”
Section: Introductionmentioning
confidence: 99%